THE INFLUENCE OF DISCUSSION TECHNIQUE TO READING COMPREHENSION AT THE TENTH GRADE STUDENTS OF SMK INSAN AQILAH - Suhendra; Ratna Hutima (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Banten, 2020)
The objective of this research is to examine a significant influence of discussion technique to reading comprehension at the tenth grade students SMK Insan Aqilah 6 Tigaraksa Kabupaten Tangerang – Banten. This is a quantitative research by using survey method. The data were gathered by conducting a test, and analyzed based on descriptive statistical analysis. The calculation mentioned above, writer found out that for variables of discussion technique, the average score is 66.13 and mode score is 80, and its standard deviation is 18.36. Meanwhile, for the variable of reading comprehension, the average score is 72 mode score is 80, and its standard deviation is 16.94. The calculation of correlation coefficient emerged the value of 0.52, and it lies between moderate or middle correlation criteria. Writer interprets through above descriptions that the tenth grade students of SMK Insan Aqilah 6 Tigaraksa Kabupaten Tangerang – Banten in general have positive achievement in discussion technique and therefore, they have ability in reading comprehension especially in English when they are learning English.